2015
DOI: 10.1038/srep07722
|View full text |Cite
|
Sign up to set email alerts
|

Water balance altered in cucumber plants infected with Fusarium oxysporum f. sp. cucumerinum

Abstract: Fusarium wilt is caused by the infection and growth of the fungus Fusarium oxysporum in the xylem of host plants. The physiological responses of cucumbers that are infected with Fusarium oxysporum f. sp. cucumerinum (FOC) was studied in pot and hydroponic experiments in a greenhouse. The results showed that although water absorption and stem hydraulic conductance decreased markedly in infected plants, large amounts of red ink accumulated in the leaves of infected cucumber plants. The transpiration rate (E) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 59 publications
(78 reference statements)
3
69
0
2
Order By: Relevance
“…The reduction in gas exchange rate and stomatal conductance has been attributed to the pathogen infection in higher plants (Wang et al 2015). The blockage of the vascular system of plants because of Fusarium infection increases resistance to water movement which may induce symptoms similar to drought stress in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in gas exchange rate and stomatal conductance has been attributed to the pathogen infection in higher plants (Wang et al 2015). The blockage of the vascular system of plants because of Fusarium infection increases resistance to water movement which may induce symptoms similar to drought stress in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The Fusarium oxysporum fungus infects the host plant via the roots or stem and induces wilting of plants due to disruption of water balance. The disturbed water balances resulted in reduced root water uptake, increased resistance to water flow through xylem elements and increased water losses from damaged cells (Wang M. et al, 2012, 2015). This type of physiological alteration in chickpea plants in response to Fusarium oxysporum infection likely regulated the expression of some of the observed changes in expression of CaAQP genes.…”
Section: Resultsmentioning
confidence: 99%
“…Sugar phloem loading occurs primarily through apoplastic and symplastic pathways (Braun et al 2014). As mentioned before, toxins produced by pathogens may damage cell membranes (Wang et al 2015a). Our study showed that the relative electrical conductivity and MDA content were highest in K-deficient rice (Fig.…”
Section: Analyzing the Primary Limiting Factors To Nsc Translocation mentioning
confidence: 98%
“…The diseased FL and FLS used for microscopic observation were prepared using the method reported by Wang et al (2015a) with some modifications. Three tillers were removed from each pot at 10 DPI and then washed with sterile water and immersed in dilute red ink for 12 h, with humidity at 60-80%.…”
Section: Microstructure Observationmentioning
confidence: 99%